UNDERSTANDING MEDICO LEGAL RESPONSIBILITIES IN POISONING CASES: INSIGHTS FROM MEDICAL INTERNS. A CROSSSECTIONAL STUDY - Pooja Gajmer; Ruchi Kumari (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Poisoning cases represent a significant portion of cases coming to the Emergency Department of any Hospital.  Most of the time, the initial management is done by the junior doctors. Treatment part is not the issue, but the medico legal part is often overlooked either due to lack of awareness and knowledge or paucity of time. Junior doctors, particularly interns who are at the threshold of independent clinical practice must possess a sound knowledge of their legal responsibilities in the management of poisoning cases, in order, to save themselves from a lot of legal implications later on.This study aimed to assess the awareness among medical interns regarding the legal duties of doctors in cases of poisoning including mandatory reporting, medicolegal documentation, sample collection and dispatching, and the ethical obligations.Material and methods: A cross sectional questionnaire based study was conducted among 150 medical interns of ACMS.Results: Results revealed that while most interns were aware of basic clinical management, significant gaps existed in their understanding of legal duties such as reporting to the police, proper documentation and maintenance of records and collection and dispatching of samples for evidence.Conclusion: The study highlights the need for improved medicolegal practical training in the undergraduate medical curriculum